The Effect Of Self Development, Teaching Experience, Teachers Certification, Infrastructure And Facilities On Class Teacher’s Professionalism At Min Jember - Qudsyi Qudsyi; Suwignyo Widagdo; Yuniorita Indah Handayani (ABM: International Journal of Administration, Business and Management, 2024)
This research aims to determine the Influence of Self-Development Training, Teaching Experience, Teacher Certification, and Infrastructure Facilities on Teacher Professionalism in State Elementary Islamic Schools (MIN) throughout Jember Regency. This research employs a quantitative approach. The population in this study comprises all teachers in MIN throughout Jember Regency, totaling 58 teachers, while the sample consists of 58 individuals. Data were collected through questionnaires distributed over a period of 3 months. Subsequently, the data were analyzed using multiple regression. The research findings indicate that self-development training and teaching experience have a positive influence on teacher professionalism. Meanwhile, teacher certification and infrastructure facilities do not have a significant effect on the level of professionalism among teachers in MIN throughout Jember Regency.